Associations between shift type, sleep, mood, and diet in a group of shift working nurses - Georgina Heath; Jillian Dorrian; Alison Coates (Nordic Association of Occupational Safety and Health (NOROSH), 2019)
OBJECTIVES: Unhealthy dietary profiles contribute to the elevated risk of chronic diseases for shift workers. There has been limited investigation into factors associated both with shift work and diet, such as sleep and mood, that may further influence food intake among shift workers. The aim of this study was to explore the relationship between shift work, sleep, mood, and diet. METHODS: Shift working nurses [N=52; 46 female; age: mean 39.8 (SD 12.4) years] participated in a 14-day, repeated measures, within- and between-subjects design study. Analyses included data from 40 nurses over 181 shifts. Food diaries were completed for a minimum of three days per shift type (morning, afternoon, night). Foodworks nutrition software was used to determine energy intake in kilojoules and macronutrient intake (as a percentage of total energy intake). Mood (happiness, anxiety, depressive mood, stress, and tiredness) was measured using visual analog scales. Sleep was estimated using actigraphy. Demographic and work-related variables (covariates) were measured using a modified version of the Standard Shiftwork Index. A path analysis was conducted using generalized structural equation modelling with a random effect of participant ID. Predictors were selected using purposive selection of covariates (an alternative to stepwise modelling) and final models included important predictors only. RESULTS: Compared to night and morning shifts, results showed that working an afternoon shift was associated with a lower energy intake (β= -1659.4, P<0.01) and lower levels of stress (β= -5.6, P<0.01). Higher levels of stress were associated with a higher energy intake (β=35.3, P<0.01) and a higher percentage of fat (ß=0.1, P=0.05) and saturated fat (β=0.1, P<0.01). Compared to the other shift types, morning shift was associated with lower carbohydrates (β= -4.3, P<0.01) and night shift was associated with lower protein (β= -2.7, P=0.03). Lower sleep efficiency was associated with a higher carbohydrate intake (β= -0.4, P<0.01) and a lower protein intake (β=0.25, P<0.01) CONCLUSIONS: Results suggest that compared to nights and mornings, afternoon shifts were associated with reduced energy consumption. Negative mood (stress, depression, and anxiety) mediated the association between shift type and energy intake. Negative mood was also associated with higher fat intake. Dietary interventions for shift workers should consider the role of mood as well as shift type.